Gerakan Sosial Ekonomi Islam Di Pedesaan: Studi Kasus Peran Baitul Maal Wat Tamwil Di Kabupaten Sragen - Thohir Yuli Kusmanto (IAIN Ponorogo, 2016)
Abstract: Islamic economic system has been experiencing rapid growth and development in Indonesia since the 1998 reform. Islamic economic discourse has become an intensive study, discussions, seminars, workshops to formulate ideal type of Islamic economics. Islamic economics is practically manifested in the form of banking, non-banking, insurance, and financial institutions. Islamic Economics has gone into rural areas in the systemic struggle among traditional economic system, a market economy and capitalistic system. Economic position of Islam becomes a middle way in terms of foundation, practices, access and capital assets. The seep of Islamic economy in the rural area is done through Baitul Maal Wat Tamwil (BMT). The process is viewed as a social movement so that it can touch rural communities. Its movement is performed by Islamic activist organizations of young generation which is affiliated with Islamic organizations or mosque activists. Early initiation was triggered by Center Incubation of Small Scale Business (Pusat Inkubasi Bisnis Usaha Kecil /PINBUK), Economic Organization, and Indonesian Muslim Scientist Association (Ikatan Cendekiawan Muslim/ ICMI) 1996. The establishment of BMT in Sragen was first done by Sragen ICMI branch. In this case, social and political conditions determined the process of formation. The primary role of BMT is as a financial institution and deposit. The role of financing has helped micro scale group of entrepreneurs,and small and medium scale groups of entrepreneurs to develop their business, and access capital. BMT encourages rural people to save their money for investment. As the Islamic financial services cooperation, BMT teaches the spirit of brotherhood and cooperation to develop Islamic economy in the rural areas. الملخص: أصبح النظام الإقتصادي الإسلامي ينمو نموّا سريعا في إندونيسيا بعد واقعة